2‐Diphenylphosphinoyl‐acetyl as a Remote Directing Group for the Highly Stereoselective Synthesis of β‐Glycosides. Issue 4 (22nd December 2021) - Liu, Xianglai; Lin, Yetong; Liu, Ao; Sun, Qianhui; Sun, Huiyong; Xu, Peng; Li, Guolong; Song, Yingying; Xie, Weijia; Sun, Haopeng; Yu, Biao; Li, Wei
Comprehensive Summary: The configuration of the anomeric glycosidic linkages is crucial for maintaining the biological functions and activities of carbohydrate molecules. However, their stereochemistry control in glycosylation represents one of the most challenging tasks in carbohydrate chemistry. In this report, the easily accessible 2‐diphenylphosphinoyl‐acetyl (DPPA) group was developed as a highly stereodirecting group for catalytic glycosylation via hydrogen‐bond mediated delivery of the alcoholic acceptors. TMSOTf‐catalyzed glycosylation with DPPA‐installed glycosyl imidate donors displayed excellent β‐selectivities and broad substrate scope, particularly practical to synthesize the challenging β‐configured 2‐deoxy and 2‐azido‐2‐deoxy glycosides from poor acceptors suffering from electron‐deficiency, steric hindrance, and structural rigidity. Chemoselective removal of the DPPA group could be readily achieved under the mild catalysis of Ni(OTf)2 without affecting acid‐ or base‐labile functional groups, facilitating a rapid conversion to biologically important molecules such as uronic acids and 2, 6‐deoxy glycosides. The application of this DPPA‐directed glycosylation was further highlighted in the complex synthesis toward saponin dioscin using 2, 4‐ O ‐glycosylated donor in a convergent manner. Abstract :